Andexanet Alfa for Factor Xa Inhibitor–Associated Intracerebral Hemorrhage: Does a Specific Reversal Agent Justify Its Cost?. (23rd November 2021) - Patel, Nikhil; Morris, Nicholas A.
Abstract : Direct oral anticoagulants have been rapidly adopted for the prevention of acute ischemic stroke and the treatment of venous thromboembolism. 1 Despite direct oral anticoagulants being associated with less incidence of intracranial hemorrhage (ICH) than vitamin K antagonists, the risk is still present, up to 2% in some observational studies. 2 In 2015, the Food and Drug Administration granted accelerated approval to idarucizumab, a monoclonal antibody that binds to dabigatran, a direct thrombin inhibitor, and neutralizes its activity. At that time, factor Xa (fXa) inhibitors (rivaroxaban and apixaban) still did not have a specific reversal agent, and guidelines recommend the off-label use of 4-factor prothrombin complex concentrates (4F-PCCs) to treat patients taking these medications and presenting with major bleeding. 3